Vesicoperineal Fistula: A Rare Rectal Cancer Treatment Complication - Moreira, Luísa (2025)
A vesicoperineal fistula is an uncommon entity, described as an aberrant tract between the bladder lumen and the cutaneous surface of the perineum. We present the case of a 78-year-old male who underwent abdominoperineal resection and chemoradiotherapy for the treatment of non-metastatic, locally advanced rectal cancer. Five years later, he developed a pelvic floor hernia and underwent perineal mesh repair. A few months postoperatively, he was diagnosed with a vesicoperineal fistula. The patient subsequently underwent fistulectomy with coccygectomy, partial cystectomy, and reconstruction using a gluteal muscle flap and skin graft. This case represents a late complication of rectal cancer treatment. Fistulas secondary to radiotherapy are complex and challenging to manage, often associated with concomitant pelvic pathology. Management should be individualized and based on a case-by-case approach.